PELATIHAN IMPLEMENTASI MEDIA BERBASIS IT PADA PEMBELAJARAN BERDIFERENSIASI KURIKULUM MERDEKA - Nurul Annisa Afriani; Amri, Nur Alim; Latief, Fadhilla; Afriani, Nurul Annisa; Azia, Andi Nur; Hasmawaty, Hasmawaty (Kreasi: Jurnal Pengabdian Masyarakat, 2024)
Differentiated learning is an approach that allows teachers to teach students by considering their individual differences. The Independent Curriculum is a curriculum that gives teachers the freedom to develop learning methods that suit students' needs. In the current digital era, the implementation of IT (Information Technology) based media can be an effective solution in differentiated learning in the Merdeka curriculum. This service activity aims to introduce and provide training on the use of technology-based media as part of the learning process in the application of differentiated learning. This service activity is based on the results of an initial study of teachers in Gantarang District, Bulukumba Regency through interview techniques and direct observation. The observation results show that educators have minimal knowledge about the use of IT media in the learning process. Apart from that, there is a lack of teacher skills in operating computer equipment, because currently only operators use computers/laptops and teachers apply learning using conventional methods. Therefore, adequate support and training is needed for teachers in implementing technology-based media in differentiated learning. The results obtained show that the implementation of IT-based media in differentiated learning in the Merdeka curriculum has several benefits. First, IT-based media can help teachers identify the needs and abilities of individual students. Second, IT-based media can provide variations in learning methods.